Morphology and elemental components of sea turtle eggshells using scanning electron microscopy - Youngsabanant, Mayuva; Nuamsukon, Suraswadee (Science, Engineering and Health Studies, 2020)
This research analyzed the morphology and elemental components of sea turtle eggshells by using quantitative and qualitative research methods. Results showed that sea turtle eggshells were composed of three layers: outer cuticle, middle, and inner fibrous layers. The morphology of the outer cuticle layer was thick, porous, and composed of aragonite to form CaCO3. The middle layer was compact and thick, and the inner layer was compact and thin. The total layer thicknesses of the green turtle (Chelonia mydas), hawksbill sea turtle (Eretmochelys imbricate), and leatherback turtle (Dermochelys coriacea) were 251.92 ± 20.86, 236.94 ± 19.26, and 237.57 ± 18.23 mm, respectively. Elemental analysis of the eggshells of all species revealed the presence of C, O, Ca, S, F, Al, Na, Cl, Si, K, P, Mg, and I. Among the elements detected, C, O, and Ca were found at high percentages to form CaCO3, which accumulated in the outer cuticle layer. Contamination of metals and non-metals, such as Mo, Br, Cu, Pb, and Pd, was found in the three types of sea turtle eggshells. This study is fundamental in providing data to manage sea turtle conservation in the future.